2002
DOI: 10.17221/5807-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Animal insulin-like growth factor binding proteins and their biological functions

Abstract: Insulin-like growth factor (IGF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Most of the circuThe insulin-like growth factor-1 and expression of its binding protein-3 in chronic hepatitis C and hepatocellular carcinoma lating IGF-1 is found in a ternary complex with IGF binding protein-3 (IGFBP-3) and the glycoprotein acid-labile subunit (ALS) (11). Binding of IGFBP-3 to IGF-1 prevents the ligand from interacting with the receptors and IGFBP-3 can modulate, both in circulation and in extracellular environment, the extent of IGF-1-dependent effects (12). IGF-1 acts primarily through the binding and the activation of IGF-1R, and ligation of IGF-1R initiates intracellular signalling cascades, involved in mitogenic, cell-survival, anti-apoptotic and transforming activities (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the circuThe insulin-like growth factor-1 and expression of its binding protein-3 in chronic hepatitis C and hepatocellular carcinoma lating IGF-1 is found in a ternary complex with IGF binding protein-3 (IGFBP-3) and the glycoprotein acid-labile subunit (ALS) (11). Binding of IGFBP-3 to IGF-1 prevents the ligand from interacting with the receptors and IGFBP-3 can modulate, both in circulation and in extracellular environment, the extent of IGF-1-dependent effects (12). IGF-1 acts primarily through the binding and the activation of IGF-1R, and ligation of IGF-1R initiates intracellular signalling cascades, involved in mitogenic, cell-survival, anti-apoptotic and transforming activities (13).…”
Section: Introductionmentioning
confidence: 99%
“…IGF-1 acts primarily through the binding and the activation of IGF-1R, and ligation of IGF-1R initiates intracellular signalling cascades, involved in mitogenic, cell-survival, anti-apoptotic and transforming activities (13). The IGFBPs may also induce mitogenesis and cell migration (12). Serum concentration of IGF-1 (S-IGF-1) in childhood grows systematically, most rapidly before and during pubescence, when it attains the highest levels, reaching a plateau in early adulthood (10,14).…”
Section: Introductionmentioning
confidence: 99%
“…The growth promoting effects of IGFs are mediated through the type I receptor, 9 and modulated by six binding proteins (IGFBPs 1-6) with high affinity for IGFs 10 as well as at least four IGFBPs with low affinity, 11,12 also known as IGFBP-related proteins (IGFBP-rp-1-4). For their IGF-dependent effects, IGFBPs have been considered as tumor suppressors, based on the assumption that their increased expression attenuates the proliferative and anti-apoptotic effects of IGFs.…”
Section: Introductionmentioning
confidence: 99%
“…The major IGFBP species is IGFBP-3, which in most physiological conditions binds more than 75% of the circulating IGF-I. Association with IGFBPs increases IGF-I half-life, as compared with free IGF-I, and IGFBPs are thought to regulate the bioavailability of IGF in target tissues (Kostecka and Blahovec, 2002). In accordance with findings of Sharma et al (1994) and Formigoni et al (1996), our results have shown that serum IGFBP-3 levels, like those of IGF-I, were the lowest just after parturition, whereas IGFBP-2 and IGFBP-4 levels increased at the same time.…”
Section: Total Protein and Albumin Concentrationsmentioning
confidence: 99%